Perceived Discrimination Trajectories and Depressive Symptoms Among Middle-Aged and Older Black Adults. Issue 5 (11th September 2020) - White, Kellee; Bell, Bethany A; Huang, Shuo J; Williams, David R
Abstract: Background and Objectives: Perceived discrimination is a risk factor for poor mental health. However, most studies measure discrimination at one time point, which does not account for heterogeneity in the cumulative patterning of exposure to discrimination. To address this gap, we examine the association between discrimination trajectories and depressive symptoms among black middle-aged and older adults. Research Design and Methods: Data were analyzed from a subsample of black Health and Retirement Study respondents (2006–2018, N = 2926, older than 50 years). General discrimination and racial discrimination trajectories were constructed based on the Everyday Discrimination Scale using repeated measures latent profile analyses. We examined the extent to which the association between discrimination trajectories are differentially associated with depressive symptoms (8-item Center for Epidemiological Studies-Depression scale) using negative binomial regression models adjusted for potential confounders. Effect modification by age and gender was tested. Results: Individuals in the persistently high (incident rate ratio [IRR]: 1.70; 95% confidence interval [CI]: 1.49–1.95) and moderate general discrimination trajectories (IRR: 1.19; 95% CI: 1.06–1.33) were more likely to have elevated depressive symptoms in comparison to those in the persistently low trajectory. This relationship was strongest among older adults aged older than 65 years. Respondents in the persistently high racial discrimination trajectory (IRR: 1.50; 95% CI: 1.29–1.73) had a higher risk of elevated depressive symptoms in comparison to respondents in the persistently low trajectory. Sensitivity analyses indicated that there was an independent association between persistently high racial discrimination trajectory class and elevated depressive symptoms, after adjusting for racial discrimination measured at a single time point. Discussion and Implications: Characterizing longitudinal patterns of perceived discrimination may facilitate the stratification of mental health risk and vulnerability among black middle-aged and older adults. Trajectories of racial discrimination may inform risk of worse depressive symptoms more accurately than a single assessment of discrimination.